PENDEKATAN SINTAGMATIK DAN PARADIGMATIK DALAM KAJIAN BAHASA - Zainuddin . (BAHAS, 2013)
ABSTRACT   This article describes the syntagmatic and paradigmatic approaches on language. It is to distinguish the two different approaches or perspectives on language, since language units may explor syntagmatic and paradigmatic relationships.The syntagmatic approach is contrasted to paradigmatic approach to study on three different levels of analysis namely, phonology, morphology, and syntax, as sub-disciplines of linguistics. In other words, the subject matters to study of the two different approaches is primarily concerned with the linguistic forms, phonemes (the study of sounds change on the level of sound structure, known as phonology),  morphemes (the study of  word structure on the level of internal word structure, known as morphology), and word (the study of how words combine to form grammatical sentences, known as syntax). This article also deals with the application of syntagmatic and paradigmatic in language teaching.   Kata Kunci : Relasi Sintagmatik dan Paradigmatik, Kajian Bahasa